Lycocasine A, a Lycopodium Alkaloid from Lycopodiastrum casuarinoides and Its Acid-Sensing Ion Channel 1a Inhibitory Activity - Shuai Jiang; Wen-Yan Li; Bei-Bei Gao; Qin-Shi Zhao (Molecules, 2024)
A novel Lycopodium alkaloid, lycocasine A (1), and seven known Lycopodium alkaloids (2–8), were isolated from Lycopodiastrum casuarinoides. Their structures were determined through NMR, HRESIMS, and X-ray diffraction analysis. Compound 1 features an unprecedented 5/6/6 tricyclic skeleton, highlighted by a 5-aza-tricyclic[6,3,1,02,6]dodecane motif. In bioactivity assays, compound 1 demonstrated weak inhibitory activity against acid-sensing ion channel 1a.